EVOLUSI ORBIT CENTAURS DAN TRANS-NEPTUNUS KE BAGIAN DALAM TATA SURYA - - B. Dermawan; - Z. Hudaya; - T. Hidayat; - M. Putra; - A. Fermita; - D. T. Wahyuningtyas; - D. Mandey; - D. Utomo (Jurnal Sains Dirgantara, 2010)
Dynamical study of Trans-Neptunian Objects (TNOs) showed that the orbital evolution of TNOs, especially for Scattered-Disk class, is closely related to Centaurs. As of 1 June 2009, there were 673 known Centaurs and TNOs whose orbits are well-determined within an uncertainty of  6.4 /decade. It is interesting to investigate a fraction of evolving Centaurs and TNOs to inner solar system regions along 1 Myr evolution under perturbations of all planets. In order to have a better knowledge about spatial distributions of Centaurs and TNOs, we generated additional four sets artificial data based on the known distribution. We find that most Centaurs show chaotic orbital evolutions and many of them are ejected out to the outer solar system. The ejected Centaurs in the first-half evolution are more numerous than that of the second-half one. This study also indicates that number of Centaurs originated from 3:2 Neptune resonance objects is more abundant at about 5  105 yr, and only ~1% Centaurs and TNOs evolve to be Mars-crossers. Keywords: Asteroids, Orbit dynamic, Centaurs, Trans-Neptunus